2018
DOI: 10.1002/sia.6426
|View full text |Cite
|
Sign up to set email alerts
|

Improved interfacial properties of carbon fiber/UHMWPE composites through surface coating on carbon fiber surface

Abstract: Carbon fibers were coated in an attempt to improve the interfacial properties between carbon fibers and ultra-high molecular weight polyethylene resin matrix. Atomic force microscopy, scanning electron microscopy, and X-ray photoelectron spectroscopy were performed to characterize the changes of carbon fiber surface. Atomic force microscopy results show that the coating of carbon fiber significantly increased the carbon fiber surface roughness. X-ray photoelectron spectroscopy indicates that silicon containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…They explained that the hydrophilic carboxylic group of benzoic acid reacted with a hydroxyl group of treated CF, which improved their compatibility with the PE matrix. Additionally, Chunzheng et al [56] reported an enhancement of the interfacial interaction between ultrahigh-molecular-weight polyethylene (UHMWPE) and CF after acid treatments. The CF was exposed to nitric acid oxidation treatments and introduced into polyoxymethylene composites (POM/CF) in an experiment conducted by Zhang et al [57].…”
Section: Chemical Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…They explained that the hydrophilic carboxylic group of benzoic acid reacted with a hydroxyl group of treated CF, which improved their compatibility with the PE matrix. Additionally, Chunzheng et al [56] reported an enhancement of the interfacial interaction between ultrahigh-molecular-weight polyethylene (UHMWPE) and CF after acid treatments. The CF was exposed to nitric acid oxidation treatments and introduced into polyoxymethylene composites (POM/CF) in an experiment conducted by Zhang et al [57].…”
Section: Chemical Treatmentsmentioning
confidence: 99%
“…However, the CF-reinforced composites have low wettability with most polymers because of their nonpolar surface characteristics. The low-interfacial bonding strength between the fibers and polymer matrices results in inadequate mechanical performance in composites [17,35,56,63,69]. The apparent ILSS of the composite is usually used to characterize adhesion quality between the fiber and matrix [39,51,56].…”
Section: Mechanical Strength and Modulus Of Cfrtpmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the strengthening modification of UHMWPE is necessary for good thermal-mechanical properties. Strengthening modification methods of UHMWPE mainly include physical modification [ 20 , 21 , 22 ], chemical modification [ 23 , 24 , 25 ], and filled composite modification [ 26 , 27 ]. For the filled composite modification, both physical and chemical methods are used.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon fiber (CF) has been successfully used to reinforce polymers to improve their mechanical properties due to their high strength, modulus, and chemical stability . Incorporation of CF into biomedical composites reduces the risk of Achille's heel which means the decrease in tensile strength derived from the addition of n‐HA into polymer matrix .…”
Section: Introductionmentioning
confidence: 99%